Identification of Two Molecular Subtypes of Hepatocellular Carcinoma Based on Dysregulated Immune LncRNAs - Lin, Hongsheng; Xie, Yangyi; Kong, Yinzhi; Yang, Li; Li, Mingfen (Frontiers in Molecular Biosciences, 2021)
Long non-coding RNAs (lncRNAs) as important regulators of gene expression also have critical functions in immune regulation. This study identified lncRNA modulators of immune-related pathways as biomarkers for hepatocellular carcinoma (HCC). The profile of lncRNA regulation in immune pathways in HCC was comprehensively mapped. To determine lncRNAs with immunomodulatory functions specific to HCC, enrichment of lncRNAs in a collection of 17 immune functions was calculated applying Gene Set Enrichment Analysis (GSEA). Unsupervised clustering of samples were performed in the R package ConsensusClusterPlus to analyze subtype survival and immunological characteristics. Enrichment of 3134 lncRNA-immune pathway pairs in both diseased and normal samples showed a total of 1,984 immunoregulatory functional lncRNAs specific to in HCC only. In addition, 18 immune-related lncRNAs were disordered in HCC, and were significantly associated with immune cell infiltration. Functional enrichment analysis indicated that the 18 dysregulated immune lncRNAs were enriched in Cytokines, Cytokine Receptors, TGFb Family Members, TNF Family Members and TNF Family Member Receptor pathways. Two molecular subtypes of hepatocellular carcinoma were identified based on 18 dysregulated immune lncRNAs. Immunological profiling showed that subtype 1 samples with higher levels of cytokine response had a better survival, but subtype 2 samples with higher levels of tumor proliferation had poorer survival. This study identified 18 HCC specific dysregulated immune lncRNAs and two HCC molecular subtypes with significant prognostic differences and immune characteristics. Those current findings help understand the function of lncRNAs and promote the identification of immunotherapy targets.